Epidemiological clinical profile of children and adolescentes victims of sexual violence accompanied in a reference center - Souza, Klisia Verona Matos de (Brazilian Journal of Sexually Transmitted Diseases, 2023)
Introduction: the World Health Organization considers sexu-al abuse one of the greatest public health problems. Such tort affects children and adolescents, often silently and may involve other types of maltreatment. Objective: evaluate the clinical and epidemiological profile of child and adolescent victims of sexual abuse in the outpatient of ACAVV (Care of Children and Adolescents Victims of Violence), University Hospital Antonio Pedro of Federal University Fluminense in Rio de Janeiro, Brazil. Methods: this is a case series of 260 patients from zero to 18 years of sexual abuse victims attended in the service the period from 2004 to 2010. Models of single and multiple logistic regression were used in statistical analysis, considering as dependent variable, chronic abuse. Results: in clinical and epidemiological profile of female sex victims predominated (89.8%), teenagers (70.8%), acute sexual abuse (60%), vaginal sex (54.9%), occurrence in the environment extrafamilial (63%) and known offenders (70.1%). The abuse usually occurred in private space (58.8%) under some kind of intimidation (66.7%). We observed a statistically signifi-cant association between the presence of other mistreatment of chronic sexual abuse (OR = 2.24, 95% CI 1.13 to 4.42), with the residence of the victims the local with the greatest chance of occurring this type of abuse. Conclusion: adolescent girls have suffered more episodes of sexual abuse and independent of the classification (acute or chronic), children and adolescents are vic-tims of males abusers, adults and acquaintances with whom they live and trust. Health professionals need to be attentive to vulne-rability factors related to episodes of violence when a situation of sexual abuse is suspected.